Clinical and Biochemical Profile of Iraqi Local Breed Cows During Pregnancy and Early Lactation - Shareef, Al-Bayati O.A.; Luaibi, Oday K. (The Iraqi Journal of Veterinary Medicine, 2020)
This study was conducted in Al-Alam region, which is located in Salah Al-Din Governorate, on first month pregnant Iraqi local cows (n-10). The follow up extended from the first month of pregnancy up to the end of the first month post-parturition during that some clinical and biochemical parameters were measured in the serum. Blood samples from the jugular vein of cows were collected monthly for the whole period of experiment and divided into four stages: early pregnancy, mid pregnancy, late pregnancy, and early lactation immediately after birth. It was observed that the temperature, respiration rate, and heart rate increased gradually and significantly (P≤0.05) with the progress of pregnancy reaching to its highest value in the last period of pregnancy and decreased after birth. The last trimester of pregnancy and the early lactation were also showed a significant decrease (P≤0.05) of the phosphorus, calcium, iron, and copper concentrations compared to the first and second trimesters of the pregnancy however, significant increases in other biochemical values (P≤0.05) were observed in urea and creatinine concentrations in the last trimester of pregnancy and early lactation. In addition to a significant decrease (P≤0.05) of the ratios of concentrations of glucose, total protein, albumin, and globulin in the last period of pregnancy compared to other periods. The decrease in the value of globulin continued until the early birth period while the study did not show any significant difference in the concentration of bilirubin between durations. Finally, values of the ALT, AST and ALP enzymes showed significant increases (P≤0.05) in their concentrations in the last period of pregnancy. It is concluded that possible changes in the biochemical parameters of the local Iraqi cows’ blood during pregnancy and early lactation are existed